Which Was Written First, Luke or Acts? - Russell, Henry G. (Harvard theological review, 1955)
New Testament scholars have almost universally assumed that Luke was written before Acts. The evidence to support this assumption is not great, and the possibility that these two books might have been written in the reverse order should also be considered. The clearest and perhaps the only evidence for the priority of Luke to Acts is to be found in Acts 1:1, where the author speaks of a “first book” which he has written, and then describes it in terms which show that he is referring to the Gospel of Luke. To this might perhaps be added the evidence of Luke 1:1–4, where the author is almost certainly giving us a preface not only to the Gospel but to Acts as well. But as Cadbury has indicated, Luke 1:1–4 may have been written after Acts had already been completed, so that this General Preface does not really give us substantial evidence for the priority of Luke. And although the secondary preface in Acts 1:1 is explicit enough about the priority of Luke, there is the possibility that it too may have been written only after the main body of both Luke and Acts had been completed. The editors of The Beginnings of Christianity, vol. V, p. 350, say, “Prefaces then, as now, were probably written after the work was completed….” This comment was made with special reference to the preface to Luke, but it might apply equally to the preface to Acts.